1995
DOI: 10.1046/j.1523-1739.1995.09061365.x
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial Buffer Zones and Wetland Conservation: A Case Study of Freshwater Turtles in a Carolina Bay

Abstract: Because freshwater wetlands often support diverse and unique species assemblages, wetland loss is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(103 citation statements)
references
References 6 publications
4
92
0
2
Order By: Relevance
“…However, our estimates are generally larger than previously published values. For example, Burke and Gibbons (1995) suggested that a 73 m zone was necessary to protect 90% of nesting and hibernation sites used by three turtle species in a single Carolina Bay in South Carolina; however, our continent-wide study suggests a 4). Our results further corroborate the 150 m zone suggested by Bodie (2001) to protect riparian areas used by riverine turtles.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, our estimates are generally larger than previously published values. For example, Burke and Gibbons (1995) suggested that a 73 m zone was necessary to protect 90% of nesting and hibernation sites used by three turtle species in a single Carolina Bay in South Carolina; however, our continent-wide study suggests a 4). Our results further corroborate the 150 m zone suggested by Bodie (2001) to protect riparian areas used by riverine turtles.…”
Section: Discussionmentioning
confidence: 70%
“…Organisms with biphasic natural histories complicate protected area development because they require both aquatic and terrestrial habitats. Specifically, core habitats of semi-aquatic species, including many amphibians (Semlitsch 1998;Pope et al, 2000;Porej et al, 2004), snakes (Roe et al, 2003), turtles (Burke and Gibbons, 1995), mammals (Kruchek, 2004), birds (Naugle et al, 1999), and insects (Bried and Ervin, 2006), encompass terrestrial uplands that are critical for conservation measures aimed at maintaining biodiversity (Semlitsch and Jensen, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…In our case study area, ecosystem management requires actors to negotiate to apply ecological criteria. These criteria depend for example on the protection of the buffer zone that will deliver multiple benefits to the wetland such as provision of habitat, and corridors to assist the movement of wildlife and reduce disturbance [66,67]; however, this action is currently not being implemented due to a fragmented institutional framework. Local level actors require state or national level endorsement when jurisdictional and institutional mismatches occur [68].…”
Section: Temporal and Spatial Arrangements Applied To Ecosystem Consementioning
confidence: 99%
“…Most of these turtles chose an older live oak and pine forest, with fewer choosing an adjacent 5-year-old clearcut. Even the most stringent wetland protection laws do not protect more than 100 ft (30.5 m) of adjacent uplands (Burke and Gibbons 1995).…”
Section: 3mentioning
confidence: 99%